Electric field distribution in porous piezoelectric materials during polarization - Michael Friswell (Acta Materialia, 2019)
High piezoelectric coupling coefficients enable the harvesting of more energy or increase the sensitivity of sensors which work using the principle of piezoelectricity. These coefficients depend on the material properties, but the manufacturing process can have a significant impact on the resulting overall coefficients. During the manufacturing process, one of the main steps is the process of polarization where a poling electric field aligns the ferroelectric domains in a similar direction in order to create a transversely isotropic material able to generate electric fields or deformations. The degree of polarization depends on multiple factors and it can strongly influence the final piezoelectric coefficients. In this paper, a study on the electric field distribution on the sensitivity of the main piezoelectric and dielectric coefficients to the polarization process is performed, focusing on porous piezoelectric materials. Different inclusion geometries are considered, namely spherical, ellipsoidal and spheres with cracks. The electric field distribution at the micro scale within a representative volume element is modelled to determine the material polarization level using the finite element method. The results show that the electric field distribution is highly dependent on the inclusion geometries and cracks and it has a noticeable impact on the equivalent piezoelectric coefficients. These results are compared with experimental measurements from published literature. Good agreement is found between the ellipsoidal model and the experimental data.